The clinico-epidemiological profile of alopecia areata: A hospital-based study in Jeddah, Saudi Arabia - Taghreed T Mahjoub (Wolters Kluwer Medknow Publications, 2020)
Background: There is a paucity of the epidemiologic studies of alopecia areata (AA) in Arab countries, especially from Saudi Arabia. Purpose: The aim was to describe the epidemiological and the clinical features of AA and its associated disease in Jeddah, Saudi Arabia. Methods: A retrospective review of medical records of 83 patients with AA seen at King Abdulaziz Medical City, Jeddah, was performed between July 2017 and July 2018. AA was classified into mild (with <10% scalp involvement and AA limited to beard area), moderate (patchy AA with <50% scalp involvement), and severe (alopecia universalis, ophiasis, alopecia totalis, and patchy AA with ≥ 50% scalp involvement). Results: The most common types of AA were mild patchy AA with <10% scalp in 35 (42.2%) patients, followed by AA limited to beard area in 24 (28.9%). The most common associated disease was atopic dermatitis which was seen in 10 (12%) patients, followed by thyroid disorder in 9 (10.8%). The most common treatment was intralesional corticosteroid (79.7% of mild and 83% of moderate) for mild and moderate and diphencyprone for severe AA (44.4%). Conclusion: Early age of onset is associated with more severe AA. The most commonly associated diseases are atopic dermatitis and thyroid disorder.